Cognitive Deficits in Adult Schizophrenia and its Association with Clinical Factors - Shabbir, Ayesha; Ali, Sohail; Sharif, Assam Muhammad Bin; Ijaz, Saman; Khan, Maria Ahmed; Nohman, Malik (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess cognitive deficits, their severity and associated clinical factors in adult patients of Schizophrenia, and to compare them with controls in psychiatric setups of Gilgit and Rawalpindi.Study Design: Comparative cross-sectional study.Place and Duration of Study: Psychiatry Department, Combined Military Hospital, Gilgit and Armed Forces Institute of Mental Health (AFIMH), Rawalpindi Pakistan, from Sep 2023 to Jan 2024.Methodology: A total of 247 individuals (147 adult Schizophrenia patients and 100 controls) were included. The Montreal Cognitive Assessment test (MoCA) Urdu 7.1 version was used to assess the cognitive deficits in both patient (cases) and control groups. Various clinical factors were also assessed for association with cognitive deficits among cases.Results: Among the total 247 study participants, the mean age was 31.97±7.63 years. One hundred and seventy-eight (27.9%) individuals were male and 69(27.9%) were females. Average MoCA score of the control group was 27.56±3.30 and average MoCA score for the cases was 20.63±3.89, with highly statistically significant difference (p-value